Effects of Dietary Energy Level on the Expression of the HSL Gene in Different Tissues of Sheep - Ying-jie ZHANG; Yue-qin LIU; Shan-yan CHENG; Jie SONG (Journal of Integrative Agriculture)
A total of 36 four-mon-old hybrid lambs (Dorset×Thin-tailed Han sheep) with similar body weight (BW) were randomly allocated to three dietary treatments with different energy (7.21, 10.33 and 13.49 MJ d−1 ME) but similar protein levels. The animals were slaughtered and subcutaneous fat, longissimus dorsi muscle, femoral biceps muscle and cardiac muscle tissue samples were taken after being treated for 40 d. The samples were then subjected to quantitative PCR to determine mRNA expression of hormone-sensitive lipase (HSL) in different tissues in the laboratory. The findings showed that the abundance of HSL mRNA decreased with the elevation of dietary energy. In the subcutaneous fatty tissue, the HSL mRNA levels showed significant differences among the three groups (P<0.01); in the longissimus dorsi and femoral biceps muscles, the HSL mRNA level in the low energy group was significantly higher than that in the moderate and high energy groups (P<0.01). In the cardiac muscle, the HSL mRNA level in the moderate energy group was significantly different from the low and high energy groups (P<0.05). The number of HSL copies (Qty) in different tissues of sheep was different, it was greater in the subcutaneous fat than in longissimus dorsi muscle, femoral biceps muscle and heart.